The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1007/s10458-008-9075-4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid exploration of unknown areas through dynamic deployment of mobile and stationary sensor nodes

Abstract: When an emergency occurs within a building, it may be initially safer to send autonomous mobile nodes, instead of human responders, to explore the area and identify hazards and victims. Exploring all the area in the minimum amount of time and reporting back interesting findings to the human personnel outside the building is an essential part of rescue operations. Our assumptions are that the area map is unknown, there is no existing network infrastructure, long-range wireless communication is unreliable and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 37 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…Taking the MAF algorithm as the base for implementation of the concept again will show that without direct communication only a small amount of data communicated between two agents, which is sufficient for the base algorithm as the work of Ferranti et al in [19], [16] and our work in [20] has shown. As mentioned in the introduction additional data can contain SLAM generated maps of the environment by the different robots.…”
Section: The Concept Of Layered Communicationmentioning
confidence: 77%
See 3 more Smart Citations
“…Taking the MAF algorithm as the base for implementation of the concept again will show that without direct communication only a small amount of data communicated between two agents, which is sufficient for the base algorithm as the work of Ferranti et al in [19], [16] and our work in [20] has shown. As mentioned in the introduction additional data can contain SLAM generated maps of the environment by the different robots.…”
Section: The Concept Of Layered Communicationmentioning
confidence: 77%
“…The main drawback of this approach is that the agents may not find the markings again. To combat this problem the use of passive or active Radio-frequency identification (RFID) chips was proposed and tested in [13], [14], [15], [16].…”
Section: B Stigmergymentioning
confidence: 99%
See 2 more Smart Citations
“…Such mobile robots can also be used to collaborate with each other to detect events or track mobile targets (Hogg et al, 2002;Lambrou and Panayiotou, 2009;Mottaghi and Vaughan, 2007). Another example is search and rescue operations, where robots are used to locate survivors in environments that might be difficult to access (such as partially collapsed buildings) or too large to explore quickly by first responders (Ferranti et al, 2009).…”
Section: Introductionmentioning
confidence: 99%